Talent identification and development in South African professional football – a coach perspective - Nobre, Pedro Lacerda (School of Management Studies, 2025)
The growing complexity and competitiveness of professional sport have underscored the importance of Talent Identification and Development (TID) in football. This study examines the TID frameworks employed by South Africa's top professional male football clubs through the perspectives of coaches and key informants. This research addresses the lack of academic focus on TID practices in the Global South, highlighting the critical role of coaches in bridging theoretical frameworks and practical applications and realities. Using a qualitative, exploratory design, semi-structured interviews were conducted with 14 male professionals from seven Premier Soccer League (PSL) clubs across four provinces, including head coaches, youth coaches, and key operational staff. Thematic analysis revealed six core themes and 18 sub-themes, illustrating the interconnected and multifactorial nature of TID. Player characteristics, recruitment processes, and the complementarity between Data-driven and Intuition-driven approaches to TID emerged as pivotal elements. A significant disparity was identified between youth and senior levels, with youth football hindered by insufficient investment, infrastructure, and structured competitions. Despite the positive contribution of the under twenty-three years old national league, the Diski League, these systemic challenges limit the development of young players in South Africa. The study offers an integrated and holistic perspective on TID, evidence of presence of sophisticated professional practices, and advocates for an ecological approach to TID. It proposes three policy recommendations: improving coach development professionalization; regional youth intensive training camps for talented players; and a structured youth competition framework. These measures aim to unlock South Africa's untapped football potential, paving the way for greater success at both national and international levels.